The Integrated Role of Organizational Culture and Teamwork in Driving Employee Performance - I Komang Agus Ari Subawa; I Gede Rihayana; I Komang Oka Permadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
In an era of increasingly intense and dynamic business competition, companies are required to adapt quickly to changes in the business environment. One of the key factors determining a company’s success is the quality of employee performance. Therefore, employees are expected to continuously improve their performance so that organizational goals can be optimally achieved. Efforts companies can undertake to maintain and enhance employee performance include conducting regular performance evaluations and implementing various continuous improvement measures. These steps aim to improve the quality of human resources so that the company can survive, grow, and excel in competition. This study aims to determine the influence of organizational culture and teamwork on employee performance. The research sample includes all 31 employees of PT. ANDS BALI, with the sampling method using a saturated sampling technique. Data analysis was conducted using regression techniques. The results of the study indicate that organizational culture and teamwork have a positive and significant influence on improving employee performance.